2016
DOI: 10.1111/bjd.14415
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of the incidence of tuberous sclerosis complex in a nationwide retrospective cohort study (1997–2010)

Abstract: This is the first large-scale and longitudinal incidence study of TSC. This study provides compelling evidence that TSC mutations in humans are associated with a decreased risk of peptic ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 22 publications
2
26
3
4
Order By: Relevance
“…TSC has a prevalence of 1:20,000 and an incidence of 1:6,000-10,000 live births with no differences between ethnic groups or genders (O'Callaghan, Shiell, Osborne, & Martyn, 1998;Hong, Tu, Lin, & Lee, 2016). Here, we present an update on the genetic and genomic aspects of TSC, with a focus on clinical and laboratory practice.…”
Section: Funding Informationmentioning
confidence: 99%
“…TSC has a prevalence of 1:20,000 and an incidence of 1:6,000-10,000 live births with no differences between ethnic groups or genders (O'Callaghan, Shiell, Osborne, & Martyn, 1998;Hong, Tu, Lin, & Lee, 2016). Here, we present an update on the genetic and genomic aspects of TSC, with a focus on clinical and laboratory practice.…”
Section: Funding Informationmentioning
confidence: 99%
“…Understanding the epidemiology and disease burden of TSC is crucial for better management of the TSC population (20). Six population-based studies regarding the prevalence and mortality of TSC in the recent 15 years can be found (Table 1) (12,(21)(22)(23)(24)(25)(26). Amongst the six studies, three studies feature the prevalence of TSC in Caucasian population, with variable prevalence rate (ranges from 1 in 7,872 to 1 in 24,956).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas for Asian population, population-based prevalence studies of TSC patients can only be found in Taiwan but it varies signi cantly with time (prevalence estimated 1:2,500,000 in 1997, 1:95,136 between 2004 and 2006, and 1:63,291 in 2010) (22,23). In terms of survival, only two studies from Mayo Clinic in 1991 and Bath in 2017 addressed the mortality issue (12,27,28).…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Hong et al . in this issue of the BJD will be of great help in achieving this, now that we finally have accurate incidence and prevalence figures available for this disorder.…”
mentioning
confidence: 99%
“…In this issue of the BJD , Hong et al . successfully calculate the incidence of TSC as 0·153/100 000 and the prevalence as 1·58/10 000 . They have been able to do this because of the health insurance database registration system in Taiwan.…”
mentioning
confidence: 99%